The Influence of Using Online Shopping Applications and Digital Payment on Purchase Decisions of Klik Indomaret Application Users in Kupang City - Kamuri, Klaasvakumok J.; Giri, Yanti S.; Manongga, Irience R. A. (CV. Jala Berkat Abadi, 2025)
The purpose of this study is to examine the impact of utilizing an online shopping application (Klik Indomaret) and digital payment systems on Klik Indomaret application users' purchase decisions in Kupang City. According to the literature review, online shopping applications improve the convenience and efficiency of shopping, while digital payment solutions facilitate and secure transactions. The study used a quantitative approach with multiple linear regression analysis and included 96 Klik Indomaret users. The findings indicate that both the online shopping application and the digital payment system have a considerable influence on purchasing decisions, with a coefficient of determination of 73.6%. The debate emphasizes the value of individualized application features and transaction security in building consumer confidence. The study's conclusion underlines that the deployment of the Klik Indomaret application and digital payment systems has the potential to transform customers' long-term buying habits in Kupang City, boost customer loyalty, and support Indomaret product purchases.